Coconut Shell Waste Reduction Through Briquette Innovation: An Environmentally Friendly and Economic Improvement Solution - Lestari, Azhar Nur Dini; Latief, Abdillah Choirul; Setianingsih, Cahyani Ayu; Nibas A, ⁠Vierel Maulana; Pambudi, ⁠Priyo; Ningsih, Afrilia Setia; Lestari MS, Suci; Anam, ⁠Muhammad Ghousul; Rakhmalaely, Andien Aulia; Putri, Abhista Emilia; Idraswara, Redhatama Arya; Budiman, Arif; et al. (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2025)
Coconut shell waste is a type of organic waste that is often considered an environmental problem because it is difficult to decompose. In Purwosari Village, Wonosobo Regency, most people do not understand how to manage this waste effectively. This study aims to provide education to the people of Purwosari Village regarding the use of coconut shell waste as briquettes, which can be used as an alternative environmentally friendly energy and improve the local economy. This study uses the Participatory Action Research (PAR) approach, which involves active community participation from the problem identification stage to solution implementation. In addition, observation methods are used to understand community conditions and the potential of natural resources in the village. Observations were conducted to directly see the management of coconut shell waste and the community's response to the processing. Interviews with several community leaders were also conducted to gain perspective on the challenges and needs that exist. Socialization began by providing an understanding of the negative impacts of coconut shell waste, followed by practical training in making briquettes, which includes the carbonization process, mixing materials, molding, and drying. The results of this training showed an increase in community understanding of coconut shell waste management and its benefits as a renewable energy source. This program not only provides technical skills, but also opens up opportunities for improving the local economy through the production of environmentally friendly briquettes.